Development of a rapid and inexpensive plasma glucose estimation by two-point kinetic method based on glucose oxidase-peroxidase enzymes - Basak, Anjan (Springer India, 2007)
A rapid and inexpensive plasma glucose estimation by two-point kinetic method based on glucose oxidase and peroxidase enzymes has been developed it takes only 11/2 minutes of time and validity of the method has been discussed.